The Sage handbook of qualitative research in psychology - Willig, Carla 1964-; Rogers, Wendy Stainton (Thousand Oaks, California SAGE Inc, 2017)
The Second Edition of The SAGE Handbook of Qualitative Research in Psychology provides comprehensive coverage of the qualitative methods, strategies, and research issues in psychology. Qualitative research in psychology has been transformed since the first edition's publication. Responding to this evolving field, existing chapters have been updated while three new chapters have been added on Thematic Analysis, Interpretation, and Netnography. With a focus on methodological progress throughout, the chapters are organised into three sections: Section One: Methods Section Two: Perspectives and Techniques Section Three: Applications In the field of psychology and beyond, this handbook will constitute a valuable resource for both experienced qualitative researchers and novices for many years to come.
Keywords: Psychology -- Qualitative research; Psychology -- Research -- Methodology